A new species of Aculus mite (Acari: Eriophyidae), a potential biocontrol agent for Australian swamp stonecrop, Crassula helmsii (Crassulaceae) - Knihinicki, Danuta K.; Petanović, Radmila; Cvrković, Tatjana; Varia, Sonal (Zootaxa, 2018)
A new, gall-forming eriophyoid mite species is described from Australia. Aculus crassulae sp. nov. was found causing significant leaf deformation in Crassula helmsii (Kirk) Cockayne (Crassulaceae), a semi-aquatic, succulent plant. Native to Australia and New Zealand, this plant is now a highly invasive weed in the United Kingdom and Western Europe. The host specificity of the new mite species, and damage caused to the host plant, infer its potential to be a valuable biological control agent in countries where Australian swamp stonecrop is threatening native flora. The species description provided here, which also includes a revised diagnosis for the genus Aculus, incorporates line drawings and scanning electron micrographs (SEM). This is supplemented by a partial mitochondrial gene sequence of cytochrome c oxidase subunit I (mtCOI) and the sequence was compared with Aculus amygdali Xue & Hong and Aculus ichnocarpi (Ghosh & Chakrabarati) available in the NCBI database. Pairwise comparison of mtCOI sequences between A. crassulae sp. nov. and two congeneric species revealed 22.6% and 23.1% genetic divergence, respectively.